Spatiotemporal dynamics of retrogressive thaw slumps on the Qinghai-Tibet Plateau: integrating UAV-LiDAR and GPR - Fan Yu; Jing Luo; Fujun Niu; Zhanju Lin; Bingyan Li; Yanhu Mu; Xin Ju; Minghao Liu; Guoan Yin; Zeyong Gao; Xiaolong Zhao; Chengming Zhang (Landslides, 2025)

Cytological identification of a genus-wide chromosomal fusion-fission cycles in genus Morus - Qiming Zhou; Yahui Xuan; Jiacheng Li; Jiali Qiu; Jianglian Yuan; Chengming Fan; Zhengang Li; Shuangshuang Li; Zanmin Hu; Siwei Li; Ningjia He (Genetic Resources and Crop Evolution, 2025)

Direct Evidence of Infanticide in Wild Françoisi Langurs (Trachypithecus francoisi) Living in Limestone Habitats - Chengfei Ma; Jing Wang; Penglai Fan; Ankang Wu; Qixian Zou; Zhaohui Yang; Pan Zhang; Chengming Huang; Qihai Zhou (International Journal of Primatology, 2025)

Ordered porous copper sulfide with hollow interior for superior electrochemical CO2 to formate conversion - Wei Zhu; Longlong Fan; Qinghong Geng; Chengming Wang; Xiaoli Fan; Yingying Zhang; Cuiling Li (Chemical Engineering Journal, 2024)

Maternal parity influences the birth sex ratio and birth interval of captive Francois’ langur (Trachypithecus francoisi) - Bojun Yi; Song Wang; Tao Sun; Ruoshuang Liu; Michael J. Lawes; Li Yang; Xuefeng Liu; Yifeng Li; Chengming Huang; Qihai Zhou; Penglai Fan (Behavioral Ecology and Sociobiology, 2023)

Ordered macroporous carbonous skeletons implanted with dual-phase Co/CoFe nanoparticles for boosting electrocatalytic performance - Jun-Xuan Li; Longlong Fan; Qingfeng Hua; Qinghong Geng; Yingying Zhang; Xiaoli Fan; Lian Ma; Chengming Wang; Wei Zhu; Xiao Feng; Cuiling Li (Chemical Engineering Journal, 2023)

MUSER and IPS telescopes for solar and space weather observations - Yihua Yan; Wei Wang; Linjie Chen; Fei Liu; Jin Fan; Zhijun Chen; Lihong Geng; Chengming Tan; Suli Ma; Sha Li; Cang Su; Jing Du; et al. (Advances in Space Research, 2023)

A - p r i o r i and a - p o s t e r i o r studies of filtered probability density function models and NO formation prediction in turbulent stratified premixed combustion using machine learning - Jiahao Ren; Haiou Wang; Chengming Wang; Kun Luo; Jianren Fan (Fuel, 2023)

Botryosphaerialean fungi causing canker and dieback of tree hosts from Mount Yudu in China - Meng Pan; Haiyan Zhu; Jadson D. P. Bezerra; Guido Bonthond; Chengming Tian; Xinlei Fan (Mycological Progress, 2019)

Efforts for a Circular Economy in China: A Comprehensive Review of Policies - Junming Zhu; Chengming Fan; Haijia Shi; Lei Shi (Journal of Industrial Ecology, 2019)
Summary Circular economy concepts, practices, and policies are increasingly drawing attention as important means for the pursuit of sustainable development. This article uses a conceptual framework to catalogue and investigate policy efforts for the circular economy in China. Based on the framework, policy prototypes and specific examples are identified: resource‐oriented, production‐oriented, waste, and use‐oriented and life cycle policies. A comprehensive review of 280 related policies shows that China has a long history of resource‐oriented policies and implemented production‐oriented policies very quickly after the year 2000. China's policies toward the circular economy became more comprehensive through time, with a broad engagement of government agencies, an extensive and progressive coverage of recycling opportunities, production initiatives across multiple scales, and use of different policy instruments. The continuous progress has been driven by proactive state actors and their learning from the international society. The current policy framework, however, is concerned more with the means rather than the ends of the circular economy, and relies too much on direct subsidies and other financial incentives. Policy making can be improved by more explicit consideration of the whole production life cycle and use of market‐based policy design.

Stratigraphic absorption compensation based on multiscale shearlet transform - Chengming Liu; Deli Wang; Jialin Sun; Yibin Li; Fan Yang (Acta Geophysica, 2018)

Diaporthe from walnut tree (Juglans regia) in China, with insight of the Diaporthe eres complex - XinLei Fan; Qin Yang; Jadson D. P. Bezerra; Lourdes V. Alvarez; ChengMing Tian (Mycological Progress, 2018)

Melanconis (Melanconidaceae) associated with Betula spp. in China - Xinlei Fan; Zhuo Du; Yingmei Liang; Chengming Tian (Mycological Progress, 2016)

High seroprevalence of Coxiella burnetii in dairy cattle in China - Heba S. El-Mahallawy; Patrick Kelly; Jilei Zhang; Yi Yang; Hui Zhang; Lanjing Wei; Yongjiang Mao; Zhangping Yang; Zhenwen Zhang; Weixing Fan; Chengming Wang (Tropical Animal Health and Production, 2016)

Memory cutting of adjacent coal seams based on a hidden Markov model - Wei Li; Chengming Luo; Hai Yang; Qigao Fan (Arabian Journal of Geosciences, 2014)